2012
DOI: 10.1177/0890334411424729
|View full text |Cite
|
Sign up to set email alerts
|

Sharing of Bacterial Strains Between Breast Milk and Infant Feces

Abstract: In previous years, it has been shown that human milk is a potential source of bacteria for the infant gut. The results of this work confirm the presence of the same specific bacterial strains of Bifidobacterium, Lactobacillus, and Staphylococcus in breast milk and infant fecal samples. The identity of bacteria isolated from breast milk and infant feces from 20 mother-infant pairs was investigated at the strain level. DNA from Staphylococcus, Lactobacillus, and Bifidobacterium was detected by qRTi-PCR in nearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
215
2
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 287 publications
(239 citation statements)
references
References 42 publications
11
215
2
6
Order By: Relevance
“…Although significant attention has been paid to transmission of Bifidobacterium spp. (Martín et al 2012;Makino et al 2013;Milani et al 2015), we found high transmission rates for many Bacteroides spp. We also found that late colonizing bacteria, including Blautia, Ruminococcus, Eubacterium, and Facelibacerium, were rarely transmitted from the mother.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Although significant attention has been paid to transmission of Bifidobacterium spp. (Martín et al 2012;Makino et al 2013;Milani et al 2015), we found high transmission rates for many Bacteroides spp. We also found that late colonizing bacteria, including Blautia, Ruminococcus, Eubacterium, and Facelibacerium, were rarely transmitted from the mother.…”
Section: Discussionmentioning
confidence: 66%
“…These studies did not examine whether strains are vertically transmitted, and recent work has shown that species-level analyses alone can be insufficient to resolve transmission events . Mother-to-infant transmission of specific taxa has been resolved using culture-based techniques (Tannock et al 1990;Martín et al 2012;Makino et al 2013;Milani et al 2015), but it is not clear whether these results are generalizable across microbiome species. Other studies have examined the development of the infant gut microbiome (Koenig et al 2011), including at the strain level (Luo et al 2015;Yassour et al 2016), but did not assess vertical transmission.…”
Section: Species and Strain-resolved Analyses Shed Light On Vertical mentioning
confidence: 99%
“…The genera Bifidobacterium, Lactobacillus, and Staphylococcus occur in breast milk and infant fecal samples in paired samples (18), but stronger evidence of transfer requires identifying bacteria by strain. In 20 mother-infant pairs, colonies representing each morphological type were subject to selective plating at the strain level (19). The identity of each strain was confirmed by genetic assays such as pulse field gel electrophoresis.…”
Section: Defining Human Milk Microbiotamentioning
confidence: 99%
“…Мікроорганізми порожнини конкурують із потенційно небезпечними транзиторними мікроорганізмами, які випадково потрапляють із зовнішнього середовища, формують у порожнині кишки біологічні умови, що сприяють підтримці оптимальної концентрації таксонів фізіологічної нормофлори, беруть участь у процесах метаболізму, біосинтезу, дезінтоксикації тощо [4,5]. Тому вивчення етіологічної структури кишкових інфекцій, що зумовлені умовно патогенними мікроорганізмами, а також встановлення змін популяційного рівня мікробіоти порожнини товстої кишки в дітей грудного віку, які хворі на гостру кишкову інфекцію, за природного вигодовування визначає актуальність наукової праці [6,7].…”
Section: оригинальные исследованияunclassified